2019
DOI: 10.1097/htr.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Early Elementary School Outcome in Children With a History of Traumatic Brain Injury Before Age 6 Years

Abstract: Findings indicate the importance of in-depth follow-up specialist assessments (eg, neuropsychologist and speech and language pathologists) to identify potential nuanced difficulties in children with mild complicated TBI that may be missed by general evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Equally critical are effects of injury in childhood and in older adulthood. The importance of understanding sex differences at these life stages is supported by emerging evidence of pediatric TBI effects on social cognition and communication (89,90), and sex differences in outcome from pediatric TBI more broadly; and evidence of persistent social problems in older adults (91).…”
Section: A Hypothesis For Future Studymentioning
confidence: 99%
“…Equally critical are effects of injury in childhood and in older adulthood. The importance of understanding sex differences at these life stages is supported by emerging evidence of pediatric TBI effects on social cognition and communication (89,90), and sex differences in outcome from pediatric TBI more broadly; and evidence of persistent social problems in older adults (91).…”
Section: A Hypothesis For Future Studymentioning
confidence: 99%
“…5 In the absence of a complete neurodevelopmental evaluation, cognitive delays following TBI were more likely to remain unidentified than if formal comprehensive testing was performed. 30 Caregiver report was discussed by three articles and used to measure behavioral and executive functioning 14 ; physical, cognitive, emotional, and sleep symptoms 16 ; and overall health and functioning. 31 Studies found that caregiver report within itemized questionnaires captured functional changes not traditionally evaluated by standardized assessments (e.g., sleep disturbances, incontinence, atypical behavior specific to that child).…”
Section: Evidence For Assessment Related To Speech-language Pathologymentioning
confidence: 99%
“…31 Studies found that caregiver report within itemized questionnaires captured functional changes not traditionally evaluated by standardized assessments (e.g., sleep disturbances, incontinence, atypical behavior specific to that child). 14,16 Given caregivers' familiarity with their children's functioning pre-and postinjury, as well as children's inability to accurately report symptoms, caregivers can provide critical context to a child's functioning after brain injury to inform treatment. 14,16 Evidence for Speech-Language Pathology Treatment following Early Childhood TBI Two of the included articles discussed treatment related to speech-language pathology.…”
Section: Evidence For Assessment Related To Speech-language Pathologymentioning
confidence: 99%
See 2 more Smart Citations